Anti-Inflammatory Effect of Taurine in Burned Patients - Sima Lak; Alireza Ostadrahimi; Behrooz Nagili; Mohammad Asghari-Jafarabadi; Sanaz Beigzali; Feridoon Salehi; Roxana Djafarzadeh (Tabriz University of Medical Sciences, 2015)
Purpose: Burn induced inflammatory response can be mediated by reactive oxygen metabolites and accompanied by multiple organ dysfunction. Taurine has protective effects against various inflammatory conditions. The aim of this study was to determine the effect of Taurine supplement in thermal burn victims. Methods: Thirty patients with severe thermal burns were enrolled in this randomized double-blinded clinical trial. These patients were randomly divided into two equal groups (namely Control and Taurine groups), where both received isocaloric and isonitrogenous formula. One group was supplemented with 50 mg/kg of Taurine per day for a duration of 10 days. Blood samples were obtained to measure Interleukin-10 (IL-10), high-sensitivity C-reactive protein (hs-CRP), and Tumor Necrosis Factor alpha (TNF-α) levels at the beginning and the end of the study. Results: Change in serum level of IL-10 in Taurine group was more than Control group [-13.60(-31.40, -10.40) compared to -4.00(-20.00, -0.20) respectively; P = 0.030]. This change was significant in patients with more than 30% TBSA of burn [-14.20(-31.40, -10.40) compared to -2.40(-9.60, 0.40) respectively; P = 0.013]. As for the hs-CRP and TNF-α levels, the difference between the two groups were not significant. Conclusion: Based on the results obtained, Taurine supplement showed a positive outcome on anti-inflammatory cytokine IL-10 in all burn patients. This effect was even more significant in patients with higher percentage of burn area. Taurine had no significant effect on the inflammatory marker hs-CRP and the pro-inflammatory cytokine TNF-α level. For a more thorough verification, measurement of a wider range of inflammatory cytokines in more frequent time intervals are suggested.